2017
DOI: 10.14233/ajchem.2017.20675
|View full text |Cite
|
Sign up to set email alerts
|

Fast Determination of Naringin and Hesperidin in Natural and Commercial Citrus Juices by HPLC Method

Abstract: A reversed-phase high performance chromatographic method for simultaneous determination of naringin and hesperidin in natural and commercial citrus juices was developed. The separation was achieved on Zorbax Eclipse XDB C18 column (4.6 mm × 250 mm, 5 µm) using a acetonitrile:water:formic acid (21:78.8:0.2) solution at pH 2.5 as a mobile phase under isocratic conditions. Analysis was run at a flow rate of 1 mL min -1 with a 15 min total run time at room temperature. The detection wavelength was set at 280 nm. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The peaks (Figure 6a,b) correspond to naringin have Retention time 10.812 min and peak of Naringenin has Retention time 12.289 min. Previous studies have also reported the quantification of naringin and naringenin from orange juice, grapefruit juice and tangerine juice has been done using rapid and reliable HPLC method (Buyuktuncel, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The peaks (Figure 6a,b) correspond to naringin have Retention time 10.812 min and peak of Naringenin has Retention time 12.289 min. Previous studies have also reported the quantification of naringin and naringenin from orange juice, grapefruit juice and tangerine juice has been done using rapid and reliable HPLC method (Buyuktuncel, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In this case, chromatography with different types of detectors is the most often applied method for its identification and determination with high selectivity and acceptable sensitivity. High-performance liquid chromatography (HPLC) with UV- [5][6][7][8], diode-array [9,10] and tandem massspectrometric [11][12][13] detection is usually applied for these purposes. Recently, several approaches based on ultra-HPLC with tandem mass-spectrometric detector [14,15] and high-performance thin-layer chromatography with UV- [16] and densitometric [17] detection have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, NR and p­(NR) particles were placed in 10 mL of methanol at 1 mg/mL concentration at room temperature at 300 rpm mixing rate for 1 h. Then, these solutions were filtered through an 0.45 μm syringe filter and analyzed with HPLC at 1 mL/min flow rate with 15 min run time at 40 °C column temperature employing 20 μL of injection volumes. The mobile phase was 230:768:2 mL acetonitrile/water/formic acid, in accordance with the literature …”
Section: Methodsmentioning
confidence: 99%
“…The mobile phase was 230:768:2 mL acetonitrile/water/formic acid, in accordance with the literature. 22 The structural characterizations of NR and p(NR) particles included solid-state NMR spectroscopy and FT-IR spectroscopy. NMR experiments employed a CP/MAS 13 C NMR method (JEOL ECZ500R, 11.75 T) at 6 kHz spinning rate.…”
Section: ■ Introductionmentioning
confidence: 99%